Pola Komunikasi Antara Sekolah Dan Orangtua Siswa Berkebutuhan Khusus (SBK) Di Sekolah Inklusi - Tantiani, Farah Farida (Fakultas Psikologi UIN Syarif Hidayatullah Jakarta, 2015)
Since 2009, inclusive school programs were established in many schools in Indonesia, from pre-school to higher education. Inclusive school is school who accommodate students with various ability and character due to common right to study. Meaning students with special needs may be students of regular school and study the same material as other students. Challenges emerge for school and students' parents, particularly parents of students with special needs. These challenges have been overcome by effective communication done by school and parents of students with special needs. Knowledge of how to communicate effectively and communication method is needed by school and parents, thus the same aim can be reached to help students with special needs develop optimally at inclusive school.Â DOI:Â 10.15408/tazkiya.v20i2.9175